Theoretical and Experimental Studies on Ultraviolet Nanosecond Laser Micromachining of Sapphire. Issue 1 (3rd October 2022) - Fang, Xuyang; Wang, Shuai; Li, Bin
Abstract: The micromachining of sapphire by laser has dominated research in resent years. This paper provided theoretical and experimental studies of the micromachining of sapphire based on the UV nanosecond laser. The results indicate that the ablation is dominated by the photochemical and photo-thermal through a finite element analysis. The single-pulse ablation threshold of UV nanosecond on sapphire is 15.58 J/cm 2, and the ablation threshold gradually decreases and tends to stable finally with the increase of pulse number. Furthermore, the experiment proves that the ablation morphology with a smooth surface and little molten sediment can be realized by optimizing laser processing parameters.